Design and COMSOL Simulation of Different Shaped Piezoelectric Vibration Energy Harvesters: A Study on MEMS Vibrational Energy Harvesters - Khan, Aimal; Nawaz, Muhammad Qasim; Lu, Xu (Computational And Experimental Research In Materials And Renewable Energy, 2024)
Vibrational energy harvesters, also referred to as MEMS (Micro-Electro-Mechanical Systems) piezoelectric energy harvesters, have garnered significant attention for their potential to power wireless sensor networks and low-power electronics without external power sources. Piezoelectric materials, due to their high energy conversion efficiency and seamless integration into microsystems, are widely utilized in such designs. In this study, we simulate MEMS piezoelectric energy harvesters using PZT (lead zirconate titanate) material, each constructed with a silicon core layer and PZT piezoelectric layers. The simulations, conducted using COMSOL Multiphysics, analyze the performance of cantilever-shaped harvesters under identical boundary conditions, including solid mechanics, electrostatics, and an electric circuit with a 10 kΩ resistive load. The results show that natural frequencies range from 100 Hz to 500 Hz depending on the cantilever shape, with the generated voltage varying between 1.2 V and 3.5 V and corresponding power outputs ranging from 0.2 μW to 1.5 μW. These variations highlight the influence of cantilever geometry on energy harvesting efficiency. The study also identifies specific advantages, such as higher power density and tunable frequency ranges, making these harvesters suitable for powering remote sensing devices and microscale electronics. By quantifying performance metrics and demonstrating shape-dependent benefits, this research provides valuable insights into the design and optimization of MEMS piezoelectric harvesters for diverse applications.Keywords: Piezoelectric vibration energy harvesters, COMSOL simulation, MEMS vibrational energy harvesters, bimorph design.